Pulmonary Involvement in Neuromuscular Diseases: A review - Khanbabaee, Ghamartaj; Karim Zadeh, Parvaneh; Nasehi, Mohammad Mahdi; Tabatabaii, Seyed Ahmad; pourghasem, Matin; Alaei, Fariba; Sadr, Saeed; Farahbakhsh, Nazanin; Modarresi, Seyedeh Zalfa; Khazaii, Fatemeh; et al. (Iranian Journal of Child Neurology, 2023)
Neuromuscular diseases (NMDs) affect muscle function directly or indirectly by affecting nerves or neuromuscular junctions. One of the leading causes of death in patients with NMD is respiratory muscle weakness (RMW). Respiratory involvement in patients with NMD can manifest widely, from mild failure that may initially affect only sleep to severe failure that can be life-threatening. Care approaches include arranged and precise clinical follow-ups of signs of sleep-disordered breathing, daytime hypoventilation, coughing, and swallowing disturbances. This manuscript will review the mechanisms and abnormalities of respiratory function in patients with NMD and help optimize NMD management.